On the free vibration analysis of laminated composite and sandwich plates: A review of recent literature with some numerical results - Sayyad, Atteshamuddin S.; Ghugal, Yuwaraj M. (Composite structures, 2015)
The present article reviews the recent research done on the free vibration analysis of multilayered laminated composite and sandwich plates using various methods available for the analysis of plates. Displacement fields of various displacement based shear deformation theories have been presented and compared. Also, some numerical results related to fundamental flexural mode frequencies of laminated composite and sandwich plates are presented using a trigonometric shear and normal deformation theory. The theory involves six unknown variables and does not require problem dependent shear correction factor. Governing differential equations and associated boundary conditions of the theory are derived by employing the dynamic version of the principle of virtual work. Navier-type closed-form solutions are obtained for simply supported laminated composite and sandwich plates. The present results are compared with exact elasticity solution and other higher order shear deformation theories wherever applicable. This article cites 391 references.